Hubungan Antara Kerusakan Jalan dengan Kecepatan Kendaraan (Studi Kasus pada Jalan Munif Rahman Kota Palu) - Labaso, E.R.; Ramlan, R.; Lestari, S.P.; Mashuri, M.; Rahmat, R. (Tadulako University, 2024)
Road damage indicates a condition where the structural and functional roads are no longer able to provide optimal service to traffic crossing the road. Traffic conditions and the types of vehicles that will cross a road greatly affect the design of construction planning and road pavement made. Asphalt or concrete pavement has frequent damage due to water entering the pavement so that it becomes damaged, this can be seen on Munif Rahman Street, Palu City, Central Sulawesi Province at Sta 0+000 – 2+200. The purpose of this study was to determine the relationship between vehicle speeds caused by various road damage conditions such as potholes, edge cracks, grain release, crests on Road Munif Rahman, Palu City, especially Sta. 0+000 – 2+200. The method used to determine the speed of the vehicle is the Spot Speed, and the Pavement Condition Index (PCI) method to determine the condition of the road pavement. From the results and discussion, some conclusions that can be drawn are the regression equation obtained is y = -0.0029x2 + 0.4101x + 10.841. R2 (R Square) obtained is R² = 0.3789. This means that the relationship between road damage and vehicle speed is 38% (poor), showing the relationship between the level of road damage and vehicle speed, that the lower the PCI value, the slower the vehicle speed as in Sta 1+900 to 2+000 with a PCI value of 13. (very poor) then obtained a vehicle speed of 14.611 km/hour. The results are inversely proportional to the influence of several factors in the research conditions, namely Sta. 1+300 to 1+400 with a PCI value of 33 (medium) then the vehicle speed is 26,800 km/hour, indicating that the lower the PCI value, the faster the vehicle speed, this is influenced by the driver, obstacles, and vehicle disturbances along the way. Munif Rahman street, Palu city.